1998
DOI: 10.1093/nar/26.7.1653
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of novel human and mouse genes of the recA/RAD51 recombination-repair gene family

Abstract: Genes from the recA/RAD51 family play essential roles in homologous recombination in all organisms. Using sequence homologies from eukaryotic members of this family we have identified fragments of two additional mammalian genes with homology to RAD51. Cloning the full-length cDNAs for both human and mouse genes showed that the sequences are highly conserved, and that the predicted proteins have characteristic features of this gene family. One of the novel genes (R51H2) occurs in two forms in human cDNA, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…This is interpreted as inhibition of a repair process, repair of potentially lethal damage (Iliakis, 1988), which occurs with a variable e cacy throughout the cell cycle (Beetham and Tolmach, 1984;Iliakis and Nusse, 1983b). A similar¯attening in the cell cycle dependent variation in radiosensitivity to killing is observed in irs1 cells (Cheong et al, 1994), a radiosensitive mutant isolated from V79 cells (Jones et al, 1987), and shown to be defective in XRCC2, a RAD51 homolog (Cartwright et al, 1998;Liu et al, 1998;Tambini et al, 1997). Practically identical observations regarding radiosensitivity throughout the cell cycle have recently been published in DT40 mutants de®cient in RAD54 (Takata et al, 1998).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is interpreted as inhibition of a repair process, repair of potentially lethal damage (Iliakis, 1988), which occurs with a variable e cacy throughout the cell cycle (Beetham and Tolmach, 1984;Iliakis and Nusse, 1983b). A similar¯attening in the cell cycle dependent variation in radiosensitivity to killing is observed in irs1 cells (Cheong et al, 1994), a radiosensitive mutant isolated from V79 cells (Jones et al, 1987), and shown to be defective in XRCC2, a RAD51 homolog (Cartwright et al, 1998;Liu et al, 1998;Tambini et al, 1997). Practically identical observations regarding radiosensitivity throughout the cell cycle have recently been published in DT40 mutants de®cient in RAD54 (Takata et al, 1998).…”
Section: Introductionmentioning
confidence: 72%
“…Irs1 cells corrected for XRCC2 (irs1/ XRCC2) were generated by transfecting XRCC2 cDNA in a mammalian expression vector as described (Cartwright et al, 1998). Following selection for successful transfection, complemented clones showing more than 10-fold increase in resistance to the DNA cross-linking agent mitomycin C were tested for correction with respect to radiosensitivity to killing.…”
Section: Cell Culture and Irradiationmentioning
confidence: 99%
“…Further investigation of the SHU genes in S. cerevisiae is likely to be relevant to all eukaryotes, because putative PSY3 and SHU2 homologues have recently been identified in Schizosaccharomyces pombe (rld1 ϩ and sws1 ϩ , respectively) and human cells (RAD51D and SWS1, respectively;Martin et al, 2006). RAD51D is one of the so-called human RAD51 paralogs, based on some shared sequence similarity to RAD51 (Cartwright et al, 1998a;Kawabata and Saeki, 1998;Pittman et al, 1998). Interestingly, like psy3 and shu2 mutations in S. cerevisiae, mutation of rld1 ϩ or sws1 ϩ in S. pombe also causes sensitivity to MMS (but not to other types of DNA damage) and rescues various cellular defects caused by mutation of the RecQ helicase gene, rqh1 ϩ , in S. pombe (Martin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…RAD51D is one of the so-called human RAD51 paralogs, based on some shared sequence similarity to RAD51 (Cartwright et al, 1998a;Kawabata and Saeki, 1998;Pittman et al, 1998). Interestingly, like psy3 and shu2 mutations in S. cerevisiae, mutation of rld1 ϩ or sws1 ϩ in S. pombe also causes sensitivity to MMS (but not to other types of DNA damage) and rescues various cellular defects caused by mutation of the RecQ helicase gene, rqh1 ϩ , in S. pombe (Martin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether inhibition of HDR is a component of caffeine radiosensitization, we tested wild type and two radiosensitive mutant cell lines, irs1 and irs1SF (Jones et al, 1987;Fuller and Painter, 1988), with defects in the RAD51 paralogs XRCC2 (Tambini et al, 1997;Cartwright et al, 1998;Liu et al, 1998) and XRCC3 (Tebbs et al, 1995;Liu et al, 1998), respectively, and documented defects in HDR Pierce et al, 1999). We reasoned that if caffeine acts as a radiosensitizer by selectively targeting steps in HDR, it should be less effective in cells with genetic defects in this pathway.…”
Section: Introductionmentioning
confidence: 99%